Direct functionalization of multi-walled carbon nanotubes (MWCNTs) via grafting of poly(furfuryl methacrylate) using Diels–Alder "click chemistry" and its thermoreversibility. Issue 114 (3rd November 2015) - Pramanik, Nabendu B.; Singha, Nikhil K.
Abstract : This investigation reports a simple and single step functionalization of multi-walled carbon nanotubes (MWCNTs) based upon the Diels–Alder (DA) reaction with poly(furfuryl methacrylate) (PFMA). Abstract : This investigation reports a simple and single step functionalization of multi-walled carbon nanotubes (MWCNTs) based upon the Diels–Alder (DA) reaction with poly(furfuryl methacrylate) (PFMA). In this case, at first tailor-made PFMA was synthesized via reversible addition–fragmentation chain transfer (RAFT) polymerization. This PFMA ( M n = 8500 g mol −1, Ð = 1.37) containing the reactive furfuryl group as a diene was covalently grafted onto the surface of pristine MWCNTs via DA reaction under mild conditions at room temperature (∼30 °C) as well as 80 °C without any catalyst. The successful functionalization of PFMA onto MWCNTs was confirmed by TGA, XPS spectra, FT-IR, Raman spectroscopy and HRTEM analyses. The average grafting density was calculated to be 0.012 mmol g −1 (0.025 chain nm −2 ) at room temperature and 0.025 mmol g −1 (0.055 chain nm −2 ) at 80 °C using TGA analysis. When heated at 160 °C for 5 h the DA polymer undergoes retro-DA (rDA) reaction and the polymer layer detached from the MWCNT surface. As a result the MWCNTs precipitated in the N -methyl-2-pyrrolidone (NMP) solvent. The rDA reaction was also analyzed by TEM analysis. HRTEM showed the presence of a polymer layer of 23 nm around the MWCNT surface after functionalization.